The Effect of Using Brainstorming Strategy on Developing Creative Thinking among History Department Students at the College of Education - Al-Anbar University (Journal of the College of Basic Education, 2026)
The aim of this study is to explore the impact of brainstorming strategies on enhancing creative thinking among history department students at the College of Education at Al-Anbar University. This study is based on the following question: What is the effect of using brainstorming strategies on developing creative thinking among history department students at the College of Education - Al-Anbar University?The study adopted a quasi-experimental design, which is considered the most appropriate for measuring the effect of the independent variable (brainstorming) on the dependent variable (creative thinking). A purposive sample of 40 third-year students was selected and randomly assigned to two groups: an experimental group taught using brainstorming strategies, and a control group taught using traditional methods. The researcher employed a test to assess creative thinking, which included dimensions such as fluency, flexibility, and originality, as a tool to measure the level of creative thinking before and after implementation. The validity and reliability of the tool were verified before its use. After conducting the experiment over six weeks, the data were statistically analyzed using appropriate methods, such as the independent t-test. The results showed statistically significant differences between the mean scores of the students in the two groups, favoring the experimental group, indicating that the use of brainstorming had a clear positive impact on developing creative thinking among history students. The study recommended the importance of integrating thinking strategies and developing creative skills in history teaching, as well as generalizing the use of brainstorming across various curricula due to its role in enhancing participation and increasing students' ability to generate ideas.